2019
DOI: 10.1080/0886022x.2019.1605294
|View full text |Cite
|
Sign up to set email alerts
|

Baseline proteinuria level is associated with prognosis in idiopathic membranous nephropathy

Abstract: Objectives: This study aimed to investigate the unique prognostic, clinical, and renal histopathological characteristics of patients with idiopathic membranous nephropathy (IMN) with different levels of proteinuria. Methods: This retrospective observational study included 190 IMN patients with low levels of proteinuria (low group), 193 IMN patients with medium levels of proteinuria (medium group), and 123 IMN patients with high levels of proteinuria (high group) treated betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Recently, researches from oriental cohorts all emphasized the critical role of proteinuria in IMN, which was a valuable prognostic indicator for both the clinician and patient. Attaining lower proteinuria predicted good renal survival [15][16][17]. Our data elucidated that, the incidence of remissions of the NS was significantly higher in the TAC group in the initial 3-month follow-up.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, researches from oriental cohorts all emphasized the critical role of proteinuria in IMN, which was a valuable prognostic indicator for both the clinician and patient. Attaining lower proteinuria predicted good renal survival [15][16][17]. Our data elucidated that, the incidence of remissions of the NS was significantly higher in the TAC group in the initial 3-month follow-up.…”
Section: Discussionsupporting
confidence: 54%
“…However, normal renal function was preserved in all No AKI patients with remission of NS. Renal dysfunction and heavy proteinuria have been identified as the risk factors for progression to ESRD in iMN patients in many studies [2,19,[25][26][27], which did not differentiate acute from chronic renal dysfunction. Our study found AKI was a stronger predictor of primary renal endpoint by univariate and multivariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found high expressed miR-193a, and low expressed Wilms tumor type 1 or podocalyxin was associated with poor prognosis for IMN, including elevated proteinuria or serum creatinine, and reduced glomerular filtration rate [36]. Moreover, the baseline proteinuria level in IMN patients is significantly associated with the prognosis, and high proteinuria level with poor prognosis for IMN patients [37]. Finally, the results of this study were restricted in a resource-limited environments, and additional novel treatment strategies should be further explored for improving the prognosis of IMN.…”
Section: Discussionmentioning
confidence: 99%